Changes in plasma inorganic phosphate associated with endocrine activity in Xenopus laevis - Schrire, Velva (Division of Physiological Sciences, 2020)
The plasma inorganic phosphate level may be influenced by (1) factors affecting the intermediary metabolism of phosphorus, (2) alternation in the degree of absorption of phosphorus, (3) alteration in the degree of excretion of phosphorus. In the introduction, the intermediary metabolism of phosphorus, particularly as far as the endocrine glands are concerned, is discussed in detail, whereas the absorption and excretion are but briefly outlined.